SbMYB3 transcription factor promotes root-specific flavone biosynthesis in Scutellaria baicalensis. Issue 1 (2nd December 2022) - Fang, Yumin; Liu, Jie; Zheng, Minmin; Zhu, Sanming; Pei, Tianlin; Cui, Mengying; Chang, Lijing; Xiao, Hanwen; Yang, Jun; Martin, Cathie; Zhao, Qing
Abstract: Scutellaria baicalensis Georgi ( S. baicalensis ) produces abundant root-specific flavones (RSFs), which provide various benefits to human health. We have elucidated the complete biosynthetic pathways of baicalein and wogonin. However, the transcriptional regulation of flavone biosynthesis in S. baicalensis remains unclear. We show that the SbMYB3 transcription factor functions as a transcriptional activator involved in the biosynthesis of RSFs in S. baicalensis . Yeast one-hybrid and transcriptional activation assays showed that SbMYB3 binds to the promoter of flavone synthase II-2 ( SbFNSII-2 ) and enhances its transcription. In S. baicalensis hairy roots, RNAi of SbMYB3 reduced the accumulation of baicalin and wogonoside, and SbMYB3 knockout decreased the biosynthesis of baicalein, baicalin, wogonin, and wogonoside, whereas SbMYB3 overexpression enhanced the contents of baicalein, baicalin, wogonin and wogonoside. Transcript profiling by qRT-PCR demonstrated that SbMYB3 activates SbFNSII-2 expression directly, thus leading to more abundant accumulation of RSFs. This study provides a potential target for metabolic engineering of RSFs.